Teaching the Psychology of Engagement with Beauty: State and Trait. (January 2017) - Diessner, Rhett; Kirk, Cameron; Guenthner, Crystn; Pohling, Rico; Mobasher, Saman
An undergraduate senior-level course, the psychology of beauty, taught within the positive psychology approach, was designed with the aim to increase state and trait levels of engagement with beauty among its students. The course was a service-learning course in which students were paired by the Area Agency on Aging with elders in the greater community as a practicum experience. They studied the moral beauty of the elders, learned from their wisdom, and aimed to fulfill social needs of the elders. Results suggested that in nearly every class session, students significantly increased their state levels of engagement with beauty and state levels of engagement with moral beauty during their visits to the elders' homes, both with moderate to large effect sizes. Trait levels of engagement with beauty, however, did not increase over the span of 12 weeks.